Katolik di Tanah Karo: Kabanjahe, 1942-1970an - Ranika Br Ginting (Universitas Gadjah Mada, 2014)
This research has three main goals, namelyto examine the introduction and development of Catholicism, changes to the community after conversion and the retension of the Catholic in Tanah Karo between the years of 1942 until the 1970s. The main problem is to construct the history of the missionary activities in the Batak Karo land and the social dynamics that resulted from these activities. The period in question is one that saw the conversion of the people in Tanah Karo to Catholicism. The year of 1942 represented a crisis to the missionary activities under the Japanese occupation and the forced honouring of the Japanese sun God. Since the 1950s until 1970s, the spread and number of Catholics in the area has expanded rapidly. The result of the research is that Catholicism has been successful in spreading their faith in Tanah Karo, especially in the area of Kabanjahe. This success was the result of several factors. First, the mission was able to mingle and adapt to Karo Batak society. Second, the founding of mission schools was based on the Catholic faith.